Multilayer perceptron neural network applied to the neutron transport equation for the single velocity neurocomputational approach to neutronic calculations (Brazilian Journal of Radiation Sciences (BJRS), 2024)
The performance of neutronic calculations is a fundamental process for the analysis and design of nuclear reactors. However, due to the intrinsic complexity of these calculations, their solution is nearly impossible, whether through analytical or numerical methods. This work, through the application of a four-layer multilayer perceptron artificial neural network to the neutron transport equation, demonstrates the benefits of using neural computing for electronic calculations.